KEPENTINGAN INDONESIA BELUM MERATIFIKASI KONVENSI DAN PROTOKOL BEIJING TAHUN 2010 MENGENAI KEAMANAN PENERBANGAN SIPIL - Novita Nainggolan; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research discusses about the Indonesia has not ratified the conventions and protocols Beijing in 2010 as a new international law and was formally organized as a cooperative effort of countries in the international community for the international peace and security. National security became the main factor is the implementation of international agreements. Where state actors have an important role in national and international policy makers who represent the interests of the nation. However, the crime of terrorism continues to haunt the world of international flights by using aircraft as a means to commit acts of crime. This case raises fears for all the nations of the world up to the present time, where at any time the threat of evil can befall a country's national airline. for it, is expected to allow countries to understand which policies appropriate for use as a guideline to achieve a national interest.Keywords: Convention, Protocol, National Security, Ratified